Pengaruh Iklim Kerja, Stres Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Fajar Graha Pena Makassar - Roswiyanti Roswiyanti; Muhtazib Muhtazib; Mentari Mentari (BADAN PENERBIT STIEPARI PRESS, 2021)
This research aims to determine the influence of work climate, work stress and work discipline on employee performance. PT. Graha Pena Fajar Makassar. The research method used is a statistical analysis method using SPSS 21 (Statistical Program for Social Sciences) used for this research. The data used is quantitative data collected through distributing questions (questionnaires) related to the variables studied at PT. Fajar Graha Pena Makassar. The research results show that only 1 independent variable indicator has no effect on employee performance, namely work climate, while work stress and work discipline have an effect on employee performance